Microstructure and mechanical behavior of 17-4 precipitation hardenable steel processed by selective laser melting - Rafi, H. Khalid (2014)
The mechanical behavior and the microstructural evolution of 17-4 precipitation hardenable (PH) stainless steel processed using selective laser melting have been studied. Test coupons were produced from 17-4 PH stainless steel powder in argon and nitrogen atmospheres. Characterization studies were carried out using mechanical testing, optical microscopy, scanning electron microscopy, and x-ray diffraction. The results show that post-process heat treatment is required to obtain typically desired tensile properties. Columnar grains of smaller diameters (<2 µm) emerged within the melt pool with a mixture of martensite and retained austenite phases. It was found that the phase content of the samples is greatly influenced by the powder chemistry, processing environment, and grain diameter.